2023
DOI: 10.1101/2023.04.10.23288371
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prediction of Unplanned Hospital Readmission using Clinical and Longitudinal Wearable Sensor Features

Abstract: Predictive models have been suggested as potential tools for identifying highest risk patients for hospital readmissions, in order to improve care coordination and ultimately long-term patient outcomes. However, the accuracy of current predictive models for readmission prediction is still moderate and further data enrichment is needed to identify at risk patients. This paper describes models to predict 90-day readmission, focusing on testing the predictive performance of wearable sensor features generated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…26 Other research also showed that integrating EHR with wearable data can be used in predictive models for hospital readmission. 27 Given potential variations in daily exercise, heart rate, and sleep duration, integrating data from wearable devices could augment the algorithm's effectiveness.…”
Section: Promise and Potential Of All Of Us Multi-source Datamentioning
confidence: 99%
“…26 Other research also showed that integrating EHR with wearable data can be used in predictive models for hospital readmission. 27 Given potential variations in daily exercise, heart rate, and sleep duration, integrating data from wearable devices could augment the algorithm's effectiveness.…”
Section: Promise and Potential Of All Of Us Multi-source Datamentioning
confidence: 99%